PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PROYEK PADA PRAKTIKUM ANALISIS TITRIMETRI - Muhammad Yazeer Lili (Program Pasca Sarjana UNM, 2017)
The purpose of this study was to develop the project-based learning on practicum analysis titrimetric and to obtain project-based learning tools on practicum analysis titrimetri valid, practical and effective. Development of project-based learning tools on practicum analysis titrimetric SMK-SMAK in Makassar based on the key steps in the development of 4-D model of learning which is divided into four stages, namely: define, design, develop and dissemination . Developed learning tools that RPP, BPD, LKPD and THB in validation by two experts with the results of the assessment were valid category. From the analysis of the feasibility study is in the high category with an average value of 4.09 and meet practical criteria. Activities learners, learner response, the response of teachers, teachers' ability to manage learning at the high category and the level of success in field trials showed that completeness learning XID grade students of SMK-SMAK Makassar is 86.67% met the criteria of effectiveness. Based on the criteria used to assess learning device produced namely validity, practicality and effectiveness, then the learning device developed meets the criteria for a valid, practical, and effective.